Pembelajaran Berbasis TIK Oleh GPAI Tingkat Dasar dan Menengah Di Kabupaten Lembata - Mukin, Muh. Sulaiman Rifai Aprianus (Devotion: Jurnal Pengabdian Masyarakat, 2022)
One of the successes of a school is determined by the quality of its teachers who are good at all processes carried out in schools. Teachers who can prepare good learning tools are made possible by the supervision function of school supervisors in a directed and continuous manner. Improvements are carried out periodically, and an evaluation of the implementation of the learning and supervision is required. Improvements through continuous evaluation can be carried out through supervisory duties and functions, namely monitoring, coaching, assessing, and professional guidance and training of teachers on aspects of teacher competence and the main tasks of teachers. but in fact, the knowledge and abilities of teachers in schools and their implementation in learning still need to be improved. Therefore, this kind of workshop still needs to be held. The training and mentoring method uses the workshop method